EVALUATION OF DIURETIC AND SEDATIVE ACTIVITY FOR ETHANOLIC LEAVES EXTRACT OF BASELLA ALBA L. VAR RUBRA (World Journal of Current Medical and Pharmaceutical Research, 2020)
Herbal medicine is the oldest form of health care known to mankind. Medicinal plants can be important sources of unknown chemical substances with potential therapeutic effects. The study of plant species with diuretic effects is still a fruitful research in search of new diuretic and sedative drugs. The present study was carried out to evaluate the diuretic and sedative effect of ethanolic extract of Basella alba (BAE) in wistar rats & mice by using Lipschitz model and Rota rod model respectively. The urine volume, electrolyte levels in rats and fall of time of mices from rota rod were measured. BAE showed significant (p